Development of Prototype IoT-Based Control and Monitoring System for Pakcoy - Better Swengky; Lesta; Peprizal; Rian Ardiansyah; Yosar Leman; Aldian Kurniawan (Politeknik Negeri Cilacap, 2026)
This research aims to design and develop an Internet of Things (IoT)-based automatic control and monitoring system for hydroponic plants. This system measures, displays, and regulates nutrient parameters, pH, and water volume in real-time to improve water use efficiency, nutrient stability, and plant productivity. The method used is Research and Development (R&D) with a prototyping model. This system integrates an ESP32 microcontroller with a DFRobot pH sensor, a TDS (Total Dissolved Solids) sensor, and an ultrasonic sensor to monitor water levels. Data from the sensors is processed and sent to a cloud database to be monitored and controlled through a website interface. The test results show that the system has high accuracy, with a MAPE (Mean Absolute Percentage Error) value for the pH sensor of 6.06% (93.94% accuracy), a TDS sensor of 4.81% (95.19% accuracy), and an ultrasonic sensor of 7.98% (92.02% accuracy). All MAPE values ​​are within the <10% range, indicating good system performance for automated monitoring applications. This system implementation provides an innovative solution to the limitations of conventional, manual hydroponic systems. It can serve as an initial model for the future development of IoT-based precision agriculture.